Pengaruh Harga Tiket Dan Motivasi Dalam Keputusan Berkunjung Di Event Raisa Live In Concert - Farrah Puspita Fauzy; Ulfi Maranisya (Journal of Student Research, 2024)
This research aims to analyze the influence of price and motivation in the decision to visit the 2023 raisa live in concert event. The sample used in this research used primary data with data collection methods through questionnaires distributed to 96 respondents. The data analysis technique uses quantitative descriptive analysis. Based on the research findings, it can be concluded that the Price variable does not have a significant influence on the Decision to Attend the Raisa Live In Concert event. The research results indicate that the Motivation variable has a positive and significant impact on the Decision to Attend the Raisa Live In Concert event. The results show that the Price variable has a 0.016% impact, while the Motivation variable has a 0.244% impact on the Decision to Attend.